Anestesi Spinal Pada Pasien Hidronefrosis Dextra Et Causa Ureterolithiasis Dextra - Lutfiatul Khusnia; Fachrurrazi Fachrurrazi (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Hydronephrosis is a condition widening of one or second kidneys because of enhancement of the pressure kidney. Pressure increase consequence exists in blockage like the presence of stones in the ureters (ureterolithiasis). Treatment of stones in the ducts can done with surgery so that needs procedure anesthesia. One of the indications of spinal anesthesia is surgery urology. The patient a 45-year-old male, based on history, examination, and supporting patient was diagnosed with hydronephrosis dextra and during the ureteroscopy (URS) process a stone was found in the ureter of the dextra. Therefore, that done lithotripsy to break up stones. In this patient, it was Spinal anesthesia with Bupivacaine 0.5% 15 mg injected using spinal needle no. 25 G in the L3 - L4 region. During the operation, vital signs in the form of pressure are also monitored for blood, pulse, and oxygen saturation every 5 minutes efficiently and continuously, and administration of intravenous fluids in the form of Ringer's lactate. During the operation the patient's condition was stable. After the operation is complete, observation continues in the recovery room, where vital signs are monitored and assessed bromage scale.